2006
DOI: 10.1038/nature04334
|View full text |Cite
|
Sign up to set email alerts
|

Wnt–Ryk signalling mediates medial–lateral retinotectal topographic mapping

Abstract: Computational modelling has suggested that at least two counteracting forces are required for establishing topographic maps. Ephrin-family proteins are required for both anterior-posterior and medial-lateral topographic mapping, but the opposing forces have not been well characterized. Wnt-family proteins are recently discovered axon guidance cues. We find that Wnt3 is expressed in a medial-lateral decreasing gradient in chick optic tectum and mouse superior colliculus. Retinal ganglion cell (RGC) axons from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
244
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(247 citation statements)
references
References 28 publications
2
244
1
Order By: Relevance
“…27,[31][32][33][34] Because the function of Ryk in the mature CNS remains completely unknown, understanding the biological relevance of Ryk expression in neurons, endothelial cells, and astrocytes close to the pial surface in the unlesioned adult spinal cord clearly requires further study, especially when it has been recently demonstrated that most Wnt ligands and its modulators are expressed in the unlesioned spinal cord, 13 and that the Wnt family of proteins is involved in different CNS physiological + microglia/macrophages (B and E) and neurofilament (NF)200 + axons (B and F). At the ring of spared tissue surrounding the wound epicenter (A and G), Ryk expression was detected in glial fibrillary acidic protein (GFAP) + astrocytes (G and H), NG2 + glial precursors (G and I), adenomatous polyposis coli (APC) + oligodendrocytes (G and J) and axons (G and K).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,[31][32][33][34] Because the function of Ryk in the mature CNS remains completely unknown, understanding the biological relevance of Ryk expression in neurons, endothelial cells, and astrocytes close to the pial surface in the unlesioned adult spinal cord clearly requires further study, especially when it has been recently demonstrated that most Wnt ligands and its modulators are expressed in the unlesioned spinal cord, 13 and that the Wnt family of proteins is involved in different CNS physiological + microglia/macrophages (B and E) and neurofilament (NF)200 + axons (B and F). At the ring of spared tissue surrounding the wound epicenter (A and G), Ryk expression was detected in glial fibrillary acidic protein (GFAP) + astrocytes (G and H), NG2 + glial precursors (G and I), adenomatous polyposis coli (APC) + oligodendrocytes (G and J) and axons (G and K).…”
Section: Discussionmentioning
confidence: 99%
“…During this period and among other functions, Ryk acts as a chemorepulsive axon guidance receptor during the establishment of major axon tracts, such as the corpus callosum and the corticospinal tract (CST), 32,33 and is vital for the generation of appropriate topographic maps of retinal ganglion cell axons. 34 Given the developmental role of Ryk as an essential regulator of axonal growth and the importance of this process in functional recovery following SCI, several studies have investigated the potential of this receptor to mediate axonal regeneration in experimental models of this neuropathological condition. 10,14 Blockage of Ryk activity, which is expressed by corticospinal axons, via intrathecal administration of a Ryk-neutralizing antibody, resulted in a significant growth of axons in the CST and enhanced functional recovery following SCI.…”
mentioning
confidence: 99%
“…Unexpectedly, the Derailed ligand was identified as Wnt5 [8]. Subsequently, it was demonstrated that Wnt5a/Ryk interactions were required for chemorepulsive axon guidance in the developing mouse brain and spinal cord [9][10][11][12].…”
Section: Ryk a Novel Wnt Receptormentioning
confidence: 99%
“…The gene encoding the Wnt receptor, Frizzled3 (Fzd3), is required for the development of major fiber tracts in the rostral central nervous system (11), and targeted disruption of Fzd3 caused axonal growth and guidance defects (12). Derailed/Ryk is another Wnt receptor that regulates axon guidance in a variety of contexts (13)(14)(15)(16).…”
mentioning
confidence: 99%